Emerging targets for anticancer vaccination: IDH - Platten, Michael; Bunse, Lukas; Wick, Wolfgang (ESMO open, 2021)
The development of anticancer vaccines as a pillar of cancer immunotherapy has been hampered by the scarcity of suitable tumor-specific antigens. While response to immune checkpoint inhibitors is driven by T cells recognizing mutated antigens, the vast majority of these neoantigens are patient-specific, mandating personalized approaches. In addition, neoantigens are often subclonal present in only a fraction of tumor cells resulting in immune evasion of neoantigen-negative tumor cells. Isocitrate dehydrogenase (IDH)1 mutations, most frequently encoding for the neomorphic protein IDH1R132H, are frequent driver mutations found in the majority of diffuse World Health Organization grade 2 and 3 gliomas. In addition, IDH1R132H generates a shared clonal neoepitope that is recognized by mutation-specific T-helper cells. A recent phase 1 trial (NOA-16, NCT02454634) demonstrated safety and immunogenicity of IDH1-vac, a long IDH1R132H peptide vaccine in patients with newly diagnosed astrocytoma and provided evidence of biological efficacy based on imaging parameters. In addition, vaccine-induced IDH1R132H-reactive tumor-infiltrating T cells were identified. Here we discuss clinical and scientific implications and future developments of IDH-directed immunotherapies.